2020
DOI: 10.1108/intr-02-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of social commerce

Abstract: PurposeDue to customers' extensive avoidance behavior, social commerce may be less successful than anticipated. This study investigates the underlying mechanism and antecedents that influence customers' avoidance of peer-generated advertisements.Design/methodology/approachBased on the general framework of avoidance behavior, we propose a theoretical model for the context of a mobile social network, with tie strength as the user-related factor and violation of shared language, advertisement relevance and inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Kahlor et al (2020) used the theory of planned behaviour to model avoidance intention toward risk information in the context of a natural threat. Avoidance intentions to be exposed by marketing communications, such as location-based advertising (Shin and Lin, 2016) and social media advertising (Li et al, 2019) were also investigated. Apart from the advertising benefits, which include the ads relevance and the sales promotions, the audiences deal with some types of dilemmas, and the hesitation to use these types of platforms by specifically using digital services involve different types of risk and uncertainty, which include privacy and safety concerns.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Kahlor et al (2020) used the theory of planned behaviour to model avoidance intention toward risk information in the context of a natural threat. Avoidance intentions to be exposed by marketing communications, such as location-based advertising (Shin and Lin, 2016) and social media advertising (Li et al, 2019) were also investigated. Apart from the advertising benefits, which include the ads relevance and the sales promotions, the audiences deal with some types of dilemmas, and the hesitation to use these types of platforms by specifically using digital services involve different types of risk and uncertainty, which include privacy and safety concerns.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to Li et al (2020), since ad relevance reflects users' perceptions of utility and usefulness, this is a suitable variable to represent ad perception in advertising. On the other hand, if the ads in the digital environment are irrelevant to the consumer, the consumer may experience a lack of attention toward ads (Riedel et al, 2018).…”
Section: Antecedent-related User Factorsmentioning
confidence: 99%
“…Another research examined tie strength as a moderator variable. It demonstrated that when tie strength was high, while the effect of violation of shared language on digital ad avoidance was weaker, the effect of ad relevance and digital ad avoidance was stronger (Li et al, 2020).…”
Section: Moderation-related User Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive social shopping features may create a more complicated shopping environment, surpassing users' cognitive processing ability, diminishing collaborative efforts and a decreasing motivation for active contribution. Finally, in reaction to the undesired encounters of overload, customers will assume avoidance behaviors or even cease buying (Li et al, 2020). In addition to information overload, social shopping features may also impede purchasing intentions by tarnishing a product's reputation.…”
Section: Introductionmentioning
confidence: 99%